Kitin Sebagai Bahan Dasar Drug Delivery: Studi Interaksi Molekul Kitin dengan Vitamin C secara Ab Initio (Chitin as Base Material of Drug Delivery: Study of Interaction Chitin Molecule with Vitamin C by Ab Initio) - Satria, Army Putra (Chem Info Journal, 2013)
The research has been done on theoritical study interaction between chitin molecule and vitamin C by ab initio. The aims of this research is to determine interaction energy between segment chitin and vitamin C in specific configuration by ab initio. The method that used is ab initio quantum mechanical calculations at theoritical level and basis sets RHF/6-31G (d, p). The result of calculation showed interaction energy between dimer chitin segment…vitamin C on first configuration has interaction energy -89,299 kJ/mol or -21,343 kkal/mol and second configuration has interaction energy -49,381 kJ/mol or -11,802 kkal/mol. Configuring the more stable is the interaction between dimer chitin and vitamin C in configuration 1 because it had a greater interaction energy than configuration 2. This proved that the configuration of one more potential use as carriers in drug delivery.